(untitled) (Research, Society and Development, 2021)
Throughout its history, the construction of road pavements, faces the loss of functional and structural characteristics, due to technological and financial obstacles. In this way, studies of new materials to be used in asphalt concrete become relevant, in order to favor the implementation of more economical maintenance, recovery and pavement design policies due to their greater long-term technical suitability, and in particular , minimize the early maintenance of these structures. In this respect, the main objective of the present work was to experimentally compare through complex module (E *) and phase angle (δ) two types of asphalt concrete, one made with asphalt composition with Portland cement (CA-REF), and the other asphalt composition with comminuted graphite (CA-GRAFC). For this, four point flexion equipment was used, using a uniaxial sinusoidal loading of compression, deformation amplitude of 50μm / m; frequencies of 0.1, 0.2, 0.5, 1, 2, 5, 10 and 20 Hz and temperatures from 0 to 40 ° C, in increments of 5 ° C. After carrying out the mechanical tests, it was found that, under the conditions analyzed, the asphalt composition with comminuted graphite becomes a promising alternative as a material applicable to road pavements, acting as a substitute for the traditional filler (Portland cement).